A new species of Heptapterus Bleeker 1858 (Siluriformes, Heptapteridae) from the Uruguay River Basin in Misiones, Northeastern Argentina - Aguilera, Gastón; Benitez, Mauricio; Terán, Guillermo Enrique; Alonso, Felipe; Mirande, Juan Marcos (Zootaxa, 2017)
In this paper we describe Heptapterus mandimbusu sp. n., a new species of heptapterid catfish from a small tributary of the Uruguay River Basin in Misiones-Argentina. This new species is distinguished from all other congeners by the unique coloration pattern with aggregated melanophores scattered on dorsal and lateral surface of body, forming conspicuous size-variable blotches, and the combination of a long interdorsal distance (13.8–18.9 % SL), 14–18 anal-fin rays, short maxillary barbels (52.2–74.5 % HL), and the adipose fin confluent with caudal fin.